STREPTOZOTOCIN-INDUCED OXIDATIVE STRESS IN DIABETIC RATS - A DEFENSIVE EFFECT OF PSYDRAX DICOCCOS - Kumar V, Ravi; Rao P, Sailaja (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The present study was aimed to evaluate the antihyperglycemic activity and in vivo antioxidant effect of methanolic extract of whole plant of Psydrax dicoccos (MEPD) belonging to the family Rubiaceae. Methods: MEPD was prepared by Soxhlet extraction. Wistar rats weighing (180–200 g) were divided into six groups (n=6), with three doses of 100 mg/kg, 200 mg/kg, and 400 mg/kg of extract. Metformin was used as a standard drug. Diabetes was induced by streptozotocin (STZ) (40–50 mg/kg, i.p) in control group. The animals were treated with different doses of extracts for 21 days, and on the 22nd day, the blood glucose levels along with antioxidant enzymes such as superoxide dismutase (SOD), catalase (CAT), and lipid peroxidase (LPO) were determined. Results: The phytochemical screening of the extract showed the presence of carbohydrates, phenolics, flavonoids, glycosides, and tannins. The methanolic extract of MEPD at the dose of 200 mg/kg body weight showed a significant reduction in blood glucose levels (**p<0.001) with the value of 151.2 mg/dl on the 22nd day at 8 h. A promising antioxidant effect was also evident from the determination of antioxidant enzymes such as SOD, CAT, and LPO. Conclusion: The P. dicoccos extract revealed a potential effect of antihyperglycemic activity and combating nature on oxidative stress induced by STZ.